An eirenic itinerary;: impressions of our tour, with addresses and papers on the unity of Christian churches - McBee, Silas (Longmans, Green, 1911)
New York to Berlin.--Russia.--Russia to Italy.--Egypt.--Palestine and Syria.--Rome to Constantinople.--Close of our tour.--France and England.--Conclusions.--Addresses and papers.